2011
DOI: 10.1007/s11103-011-9815-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolites related to mechanisms of resistance in barley against Fusarium graminearum, based on mass spectrometry

Abstract: Fusarium head blight (FHB) is an economically important disease of the family Triticeae, as, apart from yield reduction it also causes quality deterioration by producing mycotoxins. Host resistance is the most promising way to control the disease. Metabolic profiling was applied to identify resistance related (RR) metabolites against Fusarium graminearum in five FHB-resistant genotypes ('Chevron', 'H5277-44', 'H5277-164', 'M92-513' and 'M122') relative to one FHB-susceptible genotype ('Stander'). The disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 56 publications
4
92
1
Order By: Relevance
“…A number of studies using DON-producing strains of F. graminearum have tried to decipher the biological functions leading to quantitative resistance to FHB in wheat or barley. Some secondary metabolism pathways were frequently found to be associated with resistance, such as the induction of the phenylpropanoid pathway and metabolites such as Phe, p-coumarate, and sinapate (Bollina et al, 2011;Kumaraswamy et al, 2011aKumaraswamy et al, , 2011b as well as the production of conjugates of flavonoids/isoflavonoids like naringenin and kaempferol (Kumaraswamy et al, 2011a(Kumaraswamy et al, , 2011b. The induction of jasmonate-regulated allene oxide synthase and 12-oxo-phytodienoic acid reductase (Gottwald et al, 2012;Kugler et al, 2013;Xiao et al, 2013), and the related metabolites linoleic and linolenic acids, jasmonates, and traumatic acid (Bollina et al, 2011;Kumaraswamy et al, 2011a), have been described as markers of quantitative resistance to FHB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies using DON-producing strains of F. graminearum have tried to decipher the biological functions leading to quantitative resistance to FHB in wheat or barley. Some secondary metabolism pathways were frequently found to be associated with resistance, such as the induction of the phenylpropanoid pathway and metabolites such as Phe, p-coumarate, and sinapate (Bollina et al, 2011;Kumaraswamy et al, 2011aKumaraswamy et al, , 2011b as well as the production of conjugates of flavonoids/isoflavonoids like naringenin and kaempferol (Kumaraswamy et al, 2011a(Kumaraswamy et al, , 2011b. The induction of jasmonate-regulated allene oxide synthase and 12-oxo-phytodienoic acid reductase (Gottwald et al, 2012;Kugler et al, 2013;Xiao et al, 2013), and the related metabolites linoleic and linolenic acids, jasmonates, and traumatic acid (Bollina et al, 2011;Kumaraswamy et al, 2011a), have been described as markers of quantitative resistance to FHB.…”
mentioning
confidence: 99%
“…Some secondary metabolism pathways were frequently found to be associated with resistance, such as the induction of the phenylpropanoid pathway and metabolites such as Phe, p-coumarate, and sinapate (Bollina et al, 2011;Kumaraswamy et al, 2011aKumaraswamy et al, , 2011b as well as the production of conjugates of flavonoids/isoflavonoids like naringenin and kaempferol (Kumaraswamy et al, 2011a(Kumaraswamy et al, , 2011b. The induction of jasmonate-regulated allene oxide synthase and 12-oxo-phytodienoic acid reductase (Gottwald et al, 2012;Kugler et al, 2013;Xiao et al, 2013), and the related metabolites linoleic and linolenic acids, jasmonates, and traumatic acid (Bollina et al, 2011;Kumaraswamy et al, 2011a), have been described as markers of quantitative resistance to FHB. Other common features were associated with defense responses such as the induction of b-1,3-glucanases, chitinases, and thaumatin-like proteins, the scavenging of reactive oxygen species, and xenobiotic detoxification by family 1 UDP-glycosyltransferases, glutathione S-transferases, cytochrome P450-monooxygenases, and transporter detoxification (Boddu et al, 2006;Golkari et al, 2007;Jia et al, 2009;Gardiner et al, 2010;Foroud et al, 2012;Kugler et al, 2013;Xiao et al, 2013).…”
mentioning
confidence: 99%
“…FHB is of primary concern because some species commonly produce the mycotoxin deoxynivalenol (DON) which is harmful to human and animal health (Allwood et al 2010;Bollina et al 2011;Walter et al 2010).…”
Section: Hazardmentioning
confidence: 99%
“…The following studies were identified for Fusarium graminearum and Pseudomonas syringae (Bollina et al, 2011;Sghaier-Hammami et al, 2012;Walter et al, 2010). The omics studies involve matabolomics (7) or proteomics (1).…”
Section: Hazardmentioning
confidence: 99%
“…In most cases, the HPLC-MS technique was used for this purpose [29][30][31]. The present methodological study based on nontarget approach describes the development and optimization of a UHPLC-Q-TOF-MS procedure for the rapid metabolomic fingerprinting of infected and control barley samples followed by multivariate data analysis of the acquired datasets.…”
Section: Introductionmentioning
confidence: 99%